(untitled) (Innovative Technologica: Methodical Research Journal, 2023)
This article discusses the main designs of oil filters for automotive internal combustion engines, as well as an analysis of common oil filter failures. Oil filters are an important component of the lubrication system in engines that help to protect and extend the lifespan of the engine. The primary function of oil filters is to remove contaminants and debris from the engine oil to ensure smooth and efficient operation of the engine. However, oil filters can also develop faults which can lead to decreased engine performance and other engine problems. In this study, we analyzed common oil filter faults to gain a better understanding of their impact on the engine and to provide insights on how to avoid them.